(untitled) (Fiep Bulletin - online, 2014)
The present study aimed to compare the basketball jump shoot coordination of players with higher and lower height. Three basketball players with higher height (2,0 ± 0,12 m; experience 16,3 ± 5,9 years) and three with lower height (1,75 ± 0,06 m; experience 12,3 ± 1,2 years) were analyzed cinematically (2 D, 60 Hz, saggital plane) performing freethrow shoots. A biomechanical model (6 points determining 4 body’s segments) provided the angular displacement and angular velocity of the shoulder, elbow and wrist. Angular displacement and velocity behavior was compared through confidence intervals of 95% during the whole movement cycle. Players with lower height seemed to optimize the counter-movement strategy around the elbow and wrist joints to release the ball. However, the coordination adopted between the players was not different in relation to the height, where only the control parameters were different. Thus, a common movement pattern is proposed in basketball shoot as a reference in the process teachlearning between players with different heights.